Decisões estratégicas: uma aplicação da teoria dos jogos nas empresas brasileiras de geotecnologias - Martins, Bruno Damas (2014)
The geotechnology market has evolved in recent years far beyond the technological aspects and offers a wide range of activities, whether they be products and/or services. The main focus of this work is oriented to Brazilian companies that are specialized in commercialization of products (hardware and software), more precisely, the companies that form the duopoly of premium products companies in the domestic market. However, in recent years, new players have entered in this market, especially companies which distributes Chinese products, but these do not have the same technological level embedded that premium products and are focused on offering goods with low price to the market. The premium companies have suffered strong influence due to the entry of second line products in the domestic market and, due to this duopolistic environment, concentrated and highly competitive environment, the strategic decisions of a company affect the other ones and vice versa. Therefore, the main subject of this work is to analyze the strategic decision to incorporate second line products in the portfolio of the duopoly geotechnology premium companies, compared to competitive interaction and risk scenarios, through a methodology based on the assumptions of the Game Theory. Although to perform in the second line products market may appear attractive, the survey results conclude that the incorporation is unfavorable in most scenarios constructed due to the conditions given by the market, including possible penalties imposed by the parent companies. Moreover, we notice that strategic decisions must stand in opposite strategies.